2007
DOI: 10.21273/horttech.17.4.580
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plant Density on Yield and Fruit Quality of Greenhouse-grown Galia Muskmelons

Abstract: Galia-type muskmelon (Cucumis melo cv. Gal-152) was grown as a fall and spring crop to determine the effect of plant density (1.7, 2.5, 3.3, and 4.1 plants/m2) on yield, fruit quality, plant growth, and economic feasibility for producing the crop in a greenhouse. Plant density had no influence on the early or total number of fruit produced per plant. Marketable yields increased linearly from 11.0 to 20.0 kg·m−2 in fall and from 21.9 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
2
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 14 publications
(27 reference statements)
6
12
2
9
Order By: Relevance
“…Increased nutrition to the vines with increase in levels of nitrogen and increased synthesis of chlorophyll and amino acids helped in efficient uptake resulting in increased length of the fruits. Similar findings were reported by Rodriguez [16] in musk melon, Sharma [12] in cucumber, Rasul [17] in kakrol and Anil Kumar [3] in ridge gourd. The mean fruit weight was maximum with T 3 (454.03 g), followed by T 2 (431.42 g), T 1 (422.17 g) and T 8 (408.69 g).…”
Section: Discussionsupporting
confidence: 88%
“…Increased nutrition to the vines with increase in levels of nitrogen and increased synthesis of chlorophyll and amino acids helped in efficient uptake resulting in increased length of the fruits. Similar findings were reported by Rodriguez [16] in musk melon, Sharma [12] in cucumber, Rasul [17] in kakrol and Anil Kumar [3] in ridge gourd. The mean fruit weight was maximum with T 3 (454.03 g), followed by T 2 (431.42 g), T 1 (422.17 g) and T 8 (408.69 g).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the sowing in September gave the highest fruit yield (number of fruits and total fruit weight ha -1 ) followed by May and January. This agrees with Rodriguez, et al [30] who reported that the yields of muskmelon established from August to December were better than the yields obtained by Shaw, et al [31] for the plants sowed from October to February in the same location. The number of muskmelon fruits produced in this study ranges from 9861 to 12418 ha -1 which fell within the range proposed by Meena, et al [32] under proper management.…”
Section: Effects Of Sowing Dates and Npk 15-15-15 Fertilizer Applicatsupporting
confidence: 92%
“…Similarly, a few studies also showed that as within-row spacing increased, yield per plant, number of fruits per plant, weight per fruit, and percentage of soluble solids similarly increased (Bhella, 1985b;Mendlinger, 1994;Maynard and Scott, 1998). According to Rodriguez et al (2007), the mean fruit size of 'Galia' muskmelon was not affected by plant density during the fall, but was reduced linearly during the spring as the plant density increased.…”
Section: Discussionmentioning
confidence: 99%